Magicalamity - Saunders, Kate 1960-2023 (Marion Lloyd, 2011)
Tom is in shock. He's just discovered that his dad is an escaped fairy on the run. He never knew he was a demisprite, the child of a fairy and a human. Now he must trust his life to his three fairy godmothers. Their magic is dangerous, they can't stop bickering and two of them are hardened criminals
Keywords: Fairies / Juvenile fiction; Magic / Juvenile fiction; Humorous stories; Children's stories